Local Wisdom of Sasak Aristocrat and Moral Education: A Case Study from Lombok Island - Nurlaela, Nurlaela; Hadisaputra, Prosmala; Wildan, Wildan; Zaki, M.; Zuhri, M.; Zulkifli, Muh. (Sekretariat Badan Moderasi Beragama dan Pengembangan Sumber Daya Manusia (BMBPSDM) Kementerian Agama RI, 2024)
This current study examines how the local wisdom of Sasak aristocrats can enhance moral education in pesantren. This study focuses on utilising indigenous wisdom by the Sasak aristocrats to enhance moral education in pesantren. This study employs a qualitative approach with a research design centred on the case study. The study was conducted at Pondok Pesantren Selaparang in Kediri, West Lombok, and was chosen for its unique expertise in utilising advanced Sasak language and cultures. Data collection is carried out through interviews, observations, and documentation. This study employed the interactive analysis technique proposed by Miles, Huberman, and Saldana, which includes data collection, condensation, presentation, and conclusion drawing. This current study demonstrates that moral education is strengthened through the noble Sasak local knowledge at Pondok Pesantren Selaparang in Kediri, West Lombok using several approaches: 1) Implementing Sasak Alus language in Islamic lectures at pesantren; 2) Providing role models; 3) Establishing habits through daily routines; 4) Conducting speech training (muḥāḍarah); 5) Organising speech competitions; 6) Engaging students in social, cultural, and religious events. This current study contributes to enhancing moral teaching in pesantren by theoretically and practically incorporating local wisdom.